The housing conditions in Brazilian urban areas during the 1990s - Maria da Piedade Morais (Institute for Applied Economic Research (ipea), 2015)
The objective of this article is to characterize the housing conditions in Brazilian urban areas during the 1990s, based upon housing and urban indicators derived from the 1992-1999 IBGE National Household Surveys (PNAD) microdata. The paper intends to be useful as a first attempt to systematize and analyze the available information on housing in Brazil, as a cornerstone to discuss the major trends and problems of the Brazilian housing sector, in order to subsidize the formulation of public policies and programs of housing and urban development. Section 2 discusses the main characteristics of housing that justify governmental intervention in housing markets. Section 3 depicts the housing conditions in Brazilian urban areas, emphasizing the housing situation of the poor and other vulnerable groups. Section 4 analyzes the main housing problems in Brazil, such as slums formation, tenure insecurity and housing and urban infrastructure deficits. Finally, section 5 presents the conclusions and suggestions for a future research agenda on housing in Brazil, urging for better targeting and integration between the housing policy and the macroeconomic and other sectorial and social policies of the government, at the federal, state and local levels.
Keywords: R21; R31; R38; 330